Electronic Registration of Waqf Land under the PTSL Program from a Maslahah Perspective: A Study at the Indonesian Waqf Agency Office in East Java - Musleh Harry; Fakhruddin; Mahbub Ainur Rofiq; Meisy Fajarani (El-Mashlahah, 2025)
Waqf land in East Java amounts to 78,825 plots covering 5,006.23 hectares, yet its registration level remains relatively low. Of this number, only 37,940 plots (2,270.25 ha) have been certified, while 4,885 plots (2,735.98 ha) have not obtained formal legal status. This study aims to analyze the registration system for waqf land under the Complete Systematic Land Registration Program (PTSL) and the implementation of E-Registration, as well as to examine the supervision mechanisms and their legal implications. Using an empirical juridical method with a socio-legal approach, the study explores registration practices and institutional dynamics of waqf management in the field. The primary contribution of this research lies in establishing a conceptual link between digital transformation in land administration—specifically through E-Registration—and Islamic legal institutions governing waqf. The findings show that digitalizing PTSL significantly increases the number of registered waqf lands and enhances efficiency, transparency, accountability, and legal protection for both nazhir and wakif. This demonstrates that digitalization is not merely an administrative innovation but also a tool that strengthens waqf governance as part of contemporary Islamic legal reform. This study fills a gap in the literature, which has largely focused on normative aspects of waqf without examining the integration of technology into its implementation. From a policy perspective, the success of digital PTSL depends on effective E-AIW training, accurate data validation, digital outreach, and continuous monitoring.